A MULTI-SITE PROGRAM TO PROVIDE GERIATRICS TELECONSULTATION TO OLDER RURAL VETERANS (GRECC CONNECT). (8th November 2019) - Hung, William; Barczi, Steven; Colon-Emeric, cathleen; Rossi, Michelle; Dang, Stuti; Caprio, Thomas; Espinoza, Sara
Abstract: Older Veterans living in rural areas often do not have access to geriatrics team care; rural frontline providers and teams may need support to address the needs of older adults with complex chronic conditions. GRECC Connect aims to link up geriatric teams at Geriatric Research, Education and Clinical Centers (GRECCs) and rural clinics to provide geriatric consultation remotely through clinical video telehealth (CVT) and other means. GRECC Connect is established in twelve GRECCs across the country with links to rural clinics in their catchment area; consultations led to identification and meeting of care needs of older adults with complex conditions, improving medication use and reducing older adults' need for travel to long distances for consultation. In this presentation, we review the experience of establishing connections with rural clinics, impact on older adult care and adaptations needed to address local needs and contexts.